Pengaruh Electronic Word of Mouth (E-WoM) Terhadap Minat Beli pada Aplikasi Shopee (Studi Kasus Kota Bandar Lampung) - Danit Anggi Muninggar; Aulia Rahmadini (Universitas Mitra Indonesia, 2022)
A significant decrease in website visits on Shopee e-commerce can be an indicator of the weakening buying interest of Shopee consumers. This is certainly a serious problem for an e-commerce company. So this study aims to find out that the current e-WoM will have an effect on increasing the buying interest of Bandar Lampung City residents on the Shopee application. The higher and more positive the review or e-WoM effort to attract attention in the Shopee application, the higher the consumer's buying interest. This type of research is quantitative research. This research was conducted in Bandar Lampung City and the population used were Shopee application users. The data collection technique is through a questionnaire with a sample of 68 people. Based on the results of calculations using the Smart PLS software version 3.0, the results show that there is a positive and significant influence between E-WoM on product buying interest on the Shopee application in Bandar Lampung City. That way, Shopee can improve marketing strategies through E-WoM so that visits to the Shopee application increase and are followed by increased consumer buying interest. Keywords: E-WoM, Buying Interest.